Adherence to Self-Care Behaviors among Hypertensive Patients - Asiyeh Pirzadeh; Tahereh Sim Peyman; Akbar Hassanzadeh; Firoozeh Mostafavi (Mashhad University of Medical Sciences, 2019)
Background and Objective: Adherence to self-care behaviors among hypertensive patients is a major factor in hypertension management. Hence, this study aimed to determine the self-care behaviors among patients with hypertension in Isfahan. Materials and Methods:  A cross-sectional study, with 210 hypertensive patients having referred to health centers in Isfahan 2016 Multistage random sampling was applied. The H-SCALE questionnaire including data on adherence to medication, low salt diet, smoking, physical activity and weight management was completed by interview. The data were analyzed using the SPSS software, version 20. Descriptive and analytical statistics as well as the independent t-test and Chi-Square were applied. The significance level was set at 0.05. Results:  The mean age of the subjects was 57.3±8.9. More than 90% of male and more than 80% of female reported being adherent to hypertension medication. Low-salt diet adherence in male was more than female 15.4% and 6% respectively. But female were following physical activity (22.8%) more than male (11.5%). The results showed that there was a significant difference between men and women in adherence to medication (p=0.034), no smoking (p=0.001) and and physical activity (p=0.004) . Discussion: Although more than 90% of our participants adhered medication description or weight managements for self- care, but the rate of low salt diet adherence and physical activity still needs improvement. It seems that health educators should be prepared specific protocol to improve the self- care behaviors.